Medical cannabis for treatment-resistant combat PTSD - Nacasch, Nitsa; Avni, Chen; Toren, Paz (Frontiers in Psychiatry, 2023)
Targeting the endocannabinoid system may have a role in the treatment of post-traumatic stress disorder (PTSD). However, few studies have examined the effectiveness of cannabis on symptoms of PTSD, and more research is needed to ascertain cannabis’ effectiveness. In this retrospective naturalistic study, we followed 14 relatively mature (32-68 years of age), treatment-resistant, chronic combat post-traumatic patients who remained severely symptomatic despite treatment with many lines of conventional treatment prior to receiving medicinal cannabis. Our findings show that total sleep score, subjective sleep quality, and sleep duration significantly improved (p < 0.01). Total PTSD symptom score and its subdomains (intrusiveness, avoidance, and alertness) showed improvement (p < 0.05). However, there was no improvement in the frequency of nightmares (p = 0.27). The mean follow-up time was 1.1 ± 0.8 years (range of 0.5 to 3 years).